Ukraine's path to European Union membership and its long-term implications - Zsolt M. Darvas; Marek Dabrowski; Heather Grabbe; Luca Léry Moffat; André Sapir; Georg Zachmann (Bruegel, 2024)
Whether and when Ukraine accedes to the European Union will depend greatly on how and when its war with Russia ends and post-war reconstruction starts, and how the EU handles issues of governance, security, migration, trade, investment, the energy transition, decarbonisation and the EU budget. The enlargement process is likely to overlap with post-war reconstruction, increasing the EU's influence in fostering Ukraine's institutional development. Ukrainian leaders will have strong incentives to comply with the accession criteria, which the EU should use astutely to create a better-functioning economy and public institutions, especially by reducing opportunities for corruption. This will require clearer standards for rule-of-law and fundamental values, including effective tools to ensure continued compliance after accession. That is also the most effective way to ensure a positive impact of future enlargements on EU governance. The EU will also need to develop assistance programmes to help Ukraine manage post-war security challenges and to encourage Ukrainian refugees to return to the country when possible, as they will be needed for the reconstruction effort. If the current EU budget rules were applied and there were no transitional arrangements - which is unlikely - we calculate the total annual cost of Ukraine's integration into the EU budget at 0.13 percent of EU GDP, which would hardly change net recipient/payer positions of current EU members. Ukraine's entry into the EU would benefit EU GDP via trade, migration and foreign direct investment, boosting employment, production and tax revenues in the EU. The history of EU enlargement shows that the strongest motivation for difficult reforms is a credible and predictable accession process based on rewarding reforms. Both Ukraine and the EU would benefit from progressive integration of the country into EU policies, alongside the formal accession negotiations. That would show the Ukrainian public the tangible benefits of moving towards EU standards, while also bringing Ukraine into areas such as energy cooperation and decarbonisation.
Keywords: 330